A comprehensive evaluation of Chinese college students' intercultural competence. (July 2015) - Peng, Ren-Zhong; Wu, Wei-Ping; Fan, Wei-Wei
Abstract: This study attempts to investigate how the fuzzy comprehensive evaluation index system and model of assessing Chinese college students' intercultural competence are constructed based on the theories of intercultural competence and the method of fuzzy comprehensive evaluation. In the process of model-building, the Delphi method was used to examine experts' opinions concerning the importance of each index of measuring Chinese college students' intercultural competence. In the application of the model, this study collected the participants' self-reported data and the teachers' assessments of their course performance, and the authors had the self-reported data computed in the model. The comparison of the results from the fuzzy comprehensive evaluation model with those from the teachers' assessment reveal that they are basically consistent, which suggests that the fuzzy comprehensive evaluation model can be used effectively to assess Chinese college students' intercultural competence. Thus, the model in this study provides a practical method for evaluating intercultural competence, which has pedagogical implications for internationalized talent training and curriculum design in universities and educational institutions and for college students' understanding and improving their intercultural competence. In addition, the index system and model offer intercultural scholars a new non-Western perspective to doing research on the assessment model of intercultural competence in non-Western contexts. This study makes suggestions for further research on applying the index system and the model.